PEMBUATAN BUKLET PRIMATA DI HUTAN LINDUNG GUNUNG SENUJUH PADA SUBMATERI PELESTARIAN KEANEKARAGAMAN HAYATI - Apriyani, Nina; Hardigaluh, Basuki; Wahyuni, Eko Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research purposed to know the booklet’s feasibility that consist of primates in protected forest area, Gunung Senujuh as a learning media in subsubject conservation of biodiversity in grade X senior high school. This research is quantitative with descriptive method. This research divided  into two stages. First is making of booklet and the second is validation of the media. Booklet validated by five validators that are two lecturers from Biology Education FKIP Untan, and three teachers of biology X senior high school that each one from SMA Negeri 1 Sambas, SMA Negeri 1 Sajad, and SMA Negeri 1 Sejangkung. The assessing the feasibility of booklet by filling the validation forms that consist of three aspect with 11 criteria in total. Analiysis data using Content Validity Ratio (CVR) and Content Validity Indeks (CVI). Based on data analysis of validation result, with  the value of each Content Validity Ratio (CVR)  from 11 criteria is 0,99 and CVI is 0,99 so booklet is valid and feasible as a learning media . Keywords: Booklet, Conservation of Biodiversity, Feasibility, Primates.